Games that know themselves as games: notes on metafictional analysis in video games (Simbiótica. Revista Eletrônica, 2025)
This paper explores the methodological challenges in analyzing metafiction in video games, proposing a dialogue between literary theory and game studies. The text discusses how self-referentiality manifests itself in games, as narrative and mechanical elements interact with the player. Based on research into previous proposals, it highlights the challenges of building methodologies that consider the specificities and complexities of each game, such as rules, mechanics and metafictional schemes, without disregarding contributions from other areas. The article advocates a metataxonomic approach, where metafictional schemes emerge from the corpus analyzed, and a contextual one, where metafiction can be understood as a starting point for discussions about culture and society, contributing to consolidating games studies as an interdisciplinary field.
Keywords: metafiction; video games; methodology; analysis